Human rights in action : learning expert knowledge - Halme, Miia (Erik Castrén Institute monographs on international law and human rights ;, 2010)
This study combines anthropological and critical legal approaches to explore the conceptions of knowledge, expertise and learning of a network of Nordic human rights experts. It explores how the ideals of emancipation are realized in human rights action.